Perspectives on Business and Management - Bobek, Vito (IntechOpen, 2015)
With a more holistic view of the interrelationships between individuals, markets and the larger economy, leaders can make more informed decisions. Understanding past trends in light of today's particular challenges, a wider knowledge of economics also allows business leaders to create more persuasive arguments when attempting to affect positive change within an organization. Since the turn of the century, emerging markets have dramatically increased their role on the world stage, the digital revolution has strengthened, social networks have become a decisive force also in business and the voice of the people has reinvented markets and overturned governments, a sharing economy has been born, scientific advances have changed our lives and so on. All these issues and processes pose a huge challenge for leaders, and some are tackled in this book.